Analisis Optimalisasi Penempatan Tugas Karyawan Menggunakan Metode Penugasan Pada Nescafé Kiosk Tubagus Ismail - Anisa Fitri Khaeriah; Annisa Nurhaliza; Dimas Layadri Saputra; Somadi Somadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Inappropriate employee placement based on competencies can lead to an uneven workload, longer service time, and reduced operational effectiveness. This study aimed to determine the optimal employee assignment at NESCAFÉ Kiosk Tubagus Ismail Bandung using the Hungarian Method. This research employed a descriptive quantitative approach using job completion time data collected through direct observation. The analysis consisted of constructing the assignment matrix, performing row reduction, column reduction, optimality testing, determining the optimal solution, and verifying the results using POM-QM for Windows. The results showed that the optimal assignment placed Rahma as the cashier (22 minutes), Davi in beverage preparation (barista) (30 minutes), Sindi in inventory checking (33 minutes), and Fadil in store cleaning and maintenance (43 minutes), resulting in a total completion time of 128 minutes. This was more efficient than the previous assignment system, which required 1,200 minutes, resulting in a time saving of 1,072 minutes or an 89.33% improvement in operational effectiveness. The verification results using POM-QM for Windows were consistent with the manual calculations. Therefore, the Hungarian Method proved effective in producing optimal employee assignments and supporting decision-making in human resource management.